Stability of The Banking Sector: State, Problems of Security - TALIMOVA, Lyazat; KALKABAYEVA, Gauhar (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The article considers the main directions of state regulation of the banking sector of Kazakhstan at the present stage. In the article had analyzed the main quantitative and qualitative parameters of the development of second-tier banks of Kazakhstan for the last several years. Weaknesses have been identified that reduce the stability of the banking sector, including a high level of overdue debt on bank loans, dollarization of deposit sources, low net worth of banks, increased banking risks, etc. State measures have been analyzed to support the financial stability of commercial banks. Also had systematized the reasons for the activation of integration processes in the banking sector. The necessity of improving the procedure of stress testing of Kazakhstan banks is grounded. Priority directions for ensuring the stability of Kazakhstan's banking sector for the future are identified.